Assessment of Virological Contributions to COVID-19 Outcomes in a Longitudinal Cohort of Hospitalized Adults. (14th February 2022) - Simons, Lacy M; Lorenzo-Redondo, Ramon; Gibson, Meg; Kinch, Sarah L; Vandervaart, Jacob P; Reiser, Nina L; Eren, Mesut; Lux, Elizabeth; McNally, Elizabeth M; Tambur, Anat R; Vaughan, Douglas E; Bachta, Kelly E R; et al.
Abstract: Background: While several demographic and clinical correlates of coronavirus disease 2019 (COVID-19) outcome have been identified, their relationship to virological and immunological parameters remains poorly defined. Methods: To address this, we performed longitudinal collection of nasopharyngeal swabs and blood samples from a cohort of 58 hospitalized adults with COVID-19. Samples were assessed for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viral load, viral genotype, viral diversity, and antibody titer. Demographic and clinical information, including patient blood tests and several composite measures of disease severity, was extracted from electronic health records. Results: Several factors, including male sex, higher age, higher body mass index, higher 4C Mortality score, and elevated lactate dehydrogenase levels, were associated with intensive care unit admission. Of all measured parameters, only the retrospectively calculated median Deterioration Index score was significantly associated with death. While quantitative polymerase chain reaction cycle threshold (Ct) values and genotype of SARS-CoV-2 were not significantly associated with outcome, Ct value did correlate positively with C-reactive protein levels and negatively with D-dimer, lymphocyte count, and antibody titer. Intrahost viral genetic diversity remained constant through the disease course and resulted in changes in viral genotype in some participants. Conclusions: Ultimately, these results suggest that worse outcomes are driven by immune dysfunction rather than by viral load and that SARS-CoV-2 evolution in hospital settings is relatively constant over time.